Micronutrients Intake and Status during Pregnancy and Lactation - Rees, Gail (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Optimal nutrition is important during pregnancy and lactation for the health of both the mother and infant. Chronic deficiencies of both macronutrients and micronutrients are well established in developing countries. Although in developed countries overconsumption of macronutrients is a major issue, micronutrient deficiencies which occur concomitantly are no less of a concern. Furthermore in developed countries there is also the risk of excessive micronutrient intake from dietary supplements. Micronutrients have a role in fetal and neonatal health and also health in later life. Micronutrient deficiency or toxicity during pregnancy or early life can permanently affect developing tissues, resulting in adverse growth and development of the infant which is associated with chronic diseases in adulthood. An aberrant micronutrient intake during pregnancy or lactation can also have detrimental effect on the mother both in the neonatal period and in later life.